Noise barriers: possible solution for the Venezuela Ave. and Universitaria Ave.road interchange preliminary study - Gamarra Chinchay, Hugo Eliseo (2022)
A possible solution to the increase of noise waited for by the automobile flow produced by works of the road interchange of the Avenues Universitaria and Venezuela and who have not been considered in the initial proposal that comes being executed by the Metropolitan Municipality of Lima is related. The sonorous barriers are very common in the developed countries, but we see that this technology has not been introduced in our means and this work when adjacent being to the main and more important Peruvian university deserves this improvement not to affect the education processes learning (EPL).